La céramique tournée dans le domaine ibérique (vie-ier s. av. J.-C.) : une technologie sous influence ? - Alexis Gorgues (Mélanges de la Casa de Velázquez, 2013)
Technology transfers in the ancient world are often perceived as one-way processes running from a centre of technological innovation (the classical world) to more backward peripheral areas (the proto-historical domain). Taking the example of pottery production, this article challenges that notion on the basis of a study, on the one hand of the chain of production, and on the other hand of the social processes through which technical ideas circulated. While technology transfers were assuredly at work in the more general context of the colonial contacts that were established during the first half of the 1st millennium BCE, these would have fed into the indigenous technical culture rather than creating such a culture from scratch. These processes appear to have been non-linear: the tools that were imitated were adapted and reinterpreted within a new social framework. Besides, these supposedly marginal regions were also capable of innovating and playing an active role in the formation of technical know-how.